2020
DOI: 10.1101/2020.04.21.053751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circadian Rhythms of Perineuronal Net Composition

Abstract: Perineuronal Nets (PNNs) are extracellular matrix (ECM) structures that envelop neurons and regulate synaptic functions. Long thought to be stable structures, PNNs have been recently shown to respond dynamically during learning, potentially regulating the formation of new synapses. We postulated that PNNs may vary during sleep, a period of active synaptic modification. Notably, PNN components are cleaved by matrix proteases such as the protease cathepsin-S, synthesized by microglia. Cathepsin-S is expressed in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 117 publications
2
14
0
Order By: Relevance
“…A circadian contribution (vs. sleep contribution) to the diurnal rhythm is consistent with the minimal changes in PNN intensity we previously observed at ZT6 after 6 hr sleep disruption [48]. In contrast to the Pantazopoulos study in mice [49], we found no diurnal rhythm in the number of WFA-labeled PNNs but instead a diurnal rhythm in the intensity of PNNs, suggesting that perhaps very dim PNNs were not visible in the mouse study or that there are species differences in PNN expression. Importantly, the intensity of PNNs influences the extent of plasticity of their underlying neurons, based on studies in knockout mice missing a critical proteoglycan for PNN formation (link protein 1); these mice have much less intense PNNs yet exhibit delayed critical period plasticity in the visual cortex [2].…”
Section: Pnn Intensity Is Increased In the Dark Phasesupporting
confidence: 91%
See 4 more Smart Citations
“…A circadian contribution (vs. sleep contribution) to the diurnal rhythm is consistent with the minimal changes in PNN intensity we previously observed at ZT6 after 6 hr sleep disruption [48]. In contrast to the Pantazopoulos study in mice [49], we found no diurnal rhythm in the number of WFA-labeled PNNs but instead a diurnal rhythm in the intensity of PNNs, suggesting that perhaps very dim PNNs were not visible in the mouse study or that there are species differences in PNN expression. Importantly, the intensity of PNNs influences the extent of plasticity of their underlying neurons, based on studies in knockout mice missing a critical proteoglycan for PNN formation (link protein 1); these mice have much less intense PNNs yet exhibit delayed critical period plasticity in the visual cortex [2].…”
Section: Pnn Intensity Is Increased In the Dark Phasesupporting
confidence: 91%
“…The study in mice revealed that the number of PNNs in several brain regions, including in the mPFC, followed a diurnal pattern, with higher numbers of PNNs in the dark, active phase. PNN-surrounded neurons in mPFC also demonstrated a similar diurnal pattern when mice were held under conditions of constant darkness, indicating the presence of a true circadian rhythm [49]. A circadian contribution (vs. sleep contribution) to the diurnal rhythm is consistent with the minimal changes in PNN intensity we previously observed at ZT6 after 6 hr sleep disruption [48].…”
Section: Pnn Intensity Is Increased In the Dark Phasesupporting
confidence: 85%
See 3 more Smart Citations